2017
DOI: 10.1007/s00425-017-2797-2
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotope labeling and 2,3,5,4′-tetrahydroxystilbene-2-O-β-d-glucopyranoside biosynthetic pathway characterization in Fallopia multiflora

Abstract: The THSG biosynthetic pathway in F. multiflora was characterized, and enzymatic activities responsible for the resveratrol synthesis, hydroxylation, and glycosylation reactions involved in THSG biosynthesis were confirmed in vitro. The biosynthetic origin of 2,3,5,4'-tetrahydroxystilbene-2-O-β-D-glucopyranoside (THSG) and the enzymes involved in THSG biosynthesis in Fallopia multiflora were studied using stable isotope labeling and biocatalytic methods. UPLC-MS-based analyses were used to unravel the isotopolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…1), THSG may be synthesized by the hydroxylation of trans-resveratrol to form the corresponding tetrahydroxystilbene. This hypothesis was recently confirmed by our intro studies using stable isotope labeling and biocatalytic methods (Xia et al 2017). Considering the results of previous and present study, we presumed that if FmSTS1 was cotransformed with a hydroxylase from F. multiflora, THSG may probably be produced in transgenic Arabidopsis.…”
supporting
confidence: 86%
See 3 more Smart Citations
“…1), THSG may be synthesized by the hydroxylation of trans-resveratrol to form the corresponding tetrahydroxystilbene. This hypothesis was recently confirmed by our intro studies using stable isotope labeling and biocatalytic methods (Xia et al 2017). Considering the results of previous and present study, we presumed that if FmSTS1 was cotransformed with a hydroxylase from F. multiflora, THSG may probably be produced in transgenic Arabidopsis.…”
supporting
confidence: 86%
“…THSG is the main component distributed in F. multiflora. Our team has performed considerable research aimed at characterizing the THSG biosynthesis mechanism (Xia et al 2017). We previously showed that the expression pattern of FmSTS1 analyzed by Northern blot corresponded well with the THSG distribution in different tissues of F. multiflora, implying that FmSTS1 may play a crucial role in THSG biosynthesis (Sheng et al 2010).…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Stilbene includes 2,3,5,4 0 -tetrahydroxy-stilbene-2-O-b-D-glucoside (TSG) (Ruan et al 2019). TSG is the main active chemical constituent of PMR, which has therapeutic effects on the nervous, cardiovascular, digestive, endocrine, and respiratory systems (Xia et al 2018). Recently, a great number of studies have shown that TSG may induce hepatocyte damage and cause liver damage (Xing et al 2019).…”
Section: Introductionmentioning
confidence: 99%